Globale fortællinger i den skandinaviske krimi: Myter, historie, kristendom og moralfilosofi - Agger, Gunhild (Academic Quarter | Akademisk kvarter, 2011)
Gunhild Agger’s Global Tales in Scandinavian Crime Fiction - Myths, History, Christianity and Moral Philosophy presents us with some of the reasons behind the Scandinavian crime fiction success at home and globally. One of the best known reasons is that crime fictions contain a critique of liberalism and capitalism that show the downside of this ideology and this system. However, Agger claims that there are other important reasons that can help explain the worldwide success of Scandinavian crime fiction: the skillful use of common global narratives such as myths, history, Christianity and moral philosophy. For example the mythical dimension allows a deeper plot dimension, the historical dimension uses a common understanding of the periods in European history, which is a partially known at a global level, and a Christian perspective helps with a common cultural code, namely the Bible and its narratives.